2014
DOI: 10.1080/17470218.2013.874037
|View full text |Cite
|
Sign up to set email alerts
|

Age and response bias: Evidence from the strength-based mirror effect

Abstract: Performance in episodic memory is determined both by accurate retrieval from memory and by decision processes. A substantial body of literature suggests slightly poorer episodic memory accuracy for older than younger adults; however, age-related changes in the decision mechanisms in memory have received much less attention. Response bias, the willingness to endorse an item as remembered, is an important decision factor that contributes to episodic memory performance, and therefore understanding age-related cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
(97 reference statements)
5
11
0
Order By: Relevance
“…Likewise, both age groups show strength-based mirror effects (i.e. higher hit rates and lower false alarm rates for strongly vs. weakly encoded items) (Criss et al, 2014). We expand the literature by showing this ability through trial-to-trial adaptation.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Likewise, both age groups show strength-based mirror effects (i.e. higher hit rates and lower false alarm rates for strongly vs. weakly encoded items) (Criss et al, 2014). We expand the literature by showing this ability through trial-to-trial adaptation.…”
Section: Discussionsupporting
confidence: 62%
“…For instance, when a difficult test on word pairs follows an easy one, both young and older adults shift criteria to become more conservative (Pendergrass, Olfman, Schmalstig, Seder, & Light, 2012). Related work reports similar findings of intact flexibility, although older adults tend to be more conservative (Criss et al, 2014). Other work suggests relative inflexibility, such that older adults adjust criteria to a lesser extent than young to maximize payoffs (Baron & Surdy, 1990).…”
mentioning
confidence: 89%
“…Although there were overall recognition differences between young adults and older adults, the results suggest that agerelated differences in recognition cannot be solely accounted for by the reduced attentional resources of older adults. The current findings are also consistent with Criss et al (2014), who found intact SBME between older and younger adults.…”
Section: Discussionsupporting
confidence: 92%
“…According to the diffusion model approaches (see Ratcliff & Smith, 2004 , for a review), older adults typically need to collect more evidence before selecting a response compared with their younger counterparts (Ratcliff et al, 2004 ; Starns & Ratcliff, 2010 ). Moreover, evidence exists of an age-related increase in the response criterion (Criss et al, 2014 ), a parameter of the signal detection theory, which represents the willingness of the subject to report a signal in ambiguous conditions; the higher the criterion, the higher the evidence the subject requires to report a signal, indicating a more conservative strategy.…”
Section: Discussionmentioning
confidence: 99%